Construction of Transport Channels by HNTs@ZIF-67 Composites in a Mixed-Matrix Membrane for He/CH4 Separation - Jiale Zhang; Huixin Dong; Fei Guo; Huijun Yi; Xiaobin Jiang; Gaohong He; Wu Xiao (Membranes)
In this work, HNTs@ZIF-67 composites were synthesized using the in situ growth method and incorporated into 6FDA-TFMB to prepare mixed-matrix membranes (MMMs). Scanning electron microscope (SEM) and transmission electron microscope (TEM) proved that the HNTs@ZIF-67 composite not only retained the hollow structure of HNTs, but also formed a continuous ZIF-67 transport layer on the surface of HNTs. The results of gas permeability experiments showed that with the increase in HNTs@ZIF-67 incorporation, the He permeability and He/CH4 selectivity of MMMs showed a trend of increasing first and then decreasing. When the loading is 5 wt%, the He permeability and He/CH4 selectivity of MMMs reach 116 Barrer and 305, which are 22.11% and 79.41% higher than the pure 6FDA-TFMB membrane. The results of density functional theory (DFT) and Monte Carlo (MC) calculations reveal that He diffuses more easily inside ZIF-67, HNTs and 6FDA-TFMB than CH4, and ZIF-67 shows larger adsorption energy with He than HNTs and 6FDA-TFMB, indicating that He is easily adsorbed by ZIF-67 in MMMs. Based on experimental and molecular simulation results, the mechanism of HNTs@ZIF-67 improving the He/CH4 separation performance of MMMs was summarized. With the advantage of a smaller molecular kinetic diameter, He can diffuse through ZIF-67 on the tube orifice of HNTs@ZIF-67 and enter the HNTs’ hollow tube for rapid transmission. At the same time, He can also be rapidly transferred in the continuous ZIF-67 transport channel layer, which improves the He permeability and the He/CH4 selectivity of MMMs.